Combining cycle day 7 follicle count with the basal antral follicle count improves the prediction of ovarian response - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
Objective: To analyze the predictive value of cycle day 7 follicle count (CD7-FC) for poor ovarian response during IVF in women clown-regulated with a luteal start of GnRH analogue (long protocol). Design: A retrospective analysis. Setting: University hospital. Patient(s): Ninety-one consecutive IVF cycles of 82 subjects. Intervention(s): Basal levels of FSH and E-2 were determined in the spontaneous cycle before the IVF cycle. During the IVF cycle, the number of basal and CD7 follicles and CD7 endometrial thickness were determined by ultrasound, and CD7 serum E-2 levels were measured. Main Outcome Measure(s): Ovarian response determined according to the number of mature oocytes retrieved. Result(s): On receiver operating characteristic analysis, CD7-FC had the highest combination of sensitivity and specificity to detect women with poor ovarian response when compared with the basal ovarian reserve tests. When a combined basal antral FC and CD7-FC evaluation was used with the optimum cutoff values of 6.5 and 7.5, respectively, sensitivity and specificity improved to 85% and 90%, respectively. Conclusion(s): Cycle day 7 follicle count during a long IVF protocol is helpful in predicting ovarian response in combination with the antral FC. This combination has high positive and negative predictive values. This may help clinicians and women to cancel cycles earlier and decrease the psychological, financial, and medical burden of a later cancellation. (Fertil Steril(R) 2004;81:1073-8. (C) 2004 by American Society for Reproductive Medicine.).
Keywords: ovarian reserve; antral follicle count; cycle day 7 follicle count; poor response; IVF; IN-VITRO FERTILIZATION; STIMULATING-HORMONE; RESERVE; GONADOTROPIN; AGE; RESPONSIVENESS; PREGNANCY; NUMBER; WOMEN